Reality Television Shows: Entertaining, Money Minting or Tantalizing? - Shukhre, Anagha (Indian Journal of Marketing, 2010)
As the economic flood gates opened in India, a new era of entertainment revolution is being witnessed. The television continues to swamp our screens and lives alike. This has been an overall impact of globalisation and liberalization, which has led to the growth of so many new channels in India. With the emergence of many new television channels, there has been an up surge in the competition amongst each of these channels. Whether through conduction of reality shows, religious pilgrimage telecasts or carving out their niche by telecasting a variety of programmes for kids or women, each of these channels is relying heavily on creativity and out of the box thinking. Any new concept or a programme dished out on a channel - if is successful, results in a mad rat race of other television channels for showcasing similar programmes with minor alterations. It is one of the means to increase their channel ratings and the end is always to outdo the other channels. The 'similar-but-tweaked-here-and-there' shows get churned out by the cut throat competition. Indian reality shows are the latest buzzword for the television industry. Reality TV is the new mantra of television producers and channel executives. Most of the television shows which are being telecast nowadays are reality shows specializing in dancing, singing, and acting. Everything now is a competition. So fierce is this competition in the segments that almost every channel boasts of dishing out at least two to three reality shows during their prime time. The Indian reality shows have also been consistently successful in offering a wide variety. From Talent Hunt Shows, to dance dramas, to acting-flicks, talk shows, chat-shows, cookery shows...the 'reality hunt list' is endless. All such shows have engulfed most of the TV space by having a strong audience following to bail them out, as these shows make the most of the emotional quotient of the viewers.